Spectroscopic investigations under whole-cell conditions provide new insight into the metal hydride chemistry of [FeFe]-hydrogenase. Issue 18 (30th April 2020) - Mészáros, Lívia S.; Ceccaldi, Pierre; Lorenzi, Marco; Redman, Holly J.; Pfitzner, Emanuel; Heberle, Joachim; Senger, Moritz; Stripp, Sven T.; Berggren, Gustav
Abstract : The mechanism of hydrogen gas formation by [FeFe] hydrogenase is probed under whole cell conditions, revealing the formation of reactive metal hydride species under physiologically relevant conditions. Abstract : Hydrogenases are among the fastest H2 evolving catalysts known to date and have been extensively studied under in vitro conditions. Here, we report the first mechanistic investigation of an [FeFe]-hydrogenase under whole-cell conditions. Functional [FeFe]-hydrogenase from the green alga Chlamydomonas reinhardtii is generated in genetically modified Escherichia coli cells by addition of a synthetic cofactor to the growth medium. The assembly and reactivity of the resulting semi-synthetic enzyme was monitored using whole-cell electron paramagnetic resonance and Fourier-transform Infrared difference spectroscopy as well as scattering scanning near-field optical microscopy. Through a combination of gas treatments, pH titrations, and isotope editing we were able to corroborate the formation of a number of proposed catalytic intermediates in living cells, supporting their physiological relevance. Moreover, a previously incompletely characterized catalytic intermediate is reported herein, attributed to the formation of a protonated metal hydride species.